2016
DOI: 10.1063/1.4945760
|View full text |Cite
|
Sign up to set email alerts
|

Polarization charge: Theory and applications to aqueous interfaces

Abstract: When an electric field is applied across an interface, a dielectric will acquire a polarization charge layer, assumed infinitely thin in the theory of macroscopic dielectrics and also in most treatments of electrokinetic phenomena in nanoscale structures. In this work we explore the polarization charge layer in molecular detail. Various formal relations and a linear response theory for the polarization charge are presented. Properties of the polarization charge layer are studied for three aqueous interfaces: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 94 publications
2
29
0
Order By: Relevance
“…The trough value of the major peak in polarization density at this surface changes from negative number to positive number, suggesting an intense switch (or realignment) in the dipole orientation affected by the stronger E‐field. We notice that the M z ( z ) profile under the 6 V voltage difference has a similar shape as the polarization density profile of the water slab under uniform external field with a strength of 1 V/nm reported by Shi et a l., but only in a qualitative way, the surface polarization behavior, e.g ., the peak value, does not match well. Of course, to make quantitative comparison between the uniform external field simulation method and the constant potential simulation method, one has to use exactly the same system dimensions and make sure the E‐field between the electrode and the water surface (in the CPM simulation) equals the E‐field strength in the applied uniform E‐field simulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trough value of the major peak in polarization density at this surface changes from negative number to positive number, suggesting an intense switch (or realignment) in the dipole orientation affected by the stronger E‐field. We notice that the M z ( z ) profile under the 6 V voltage difference has a similar shape as the polarization density profile of the water slab under uniform external field with a strength of 1 V/nm reported by Shi et a l., but only in a qualitative way, the surface polarization behavior, e.g ., the peak value, does not match well. Of course, to make quantitative comparison between the uniform external field simulation method and the constant potential simulation method, one has to use exactly the same system dimensions and make sure the E‐field between the electrode and the water surface (in the CPM simulation) equals the E‐field strength in the applied uniform E‐field simulation.…”
Section: Resultsmentioning
confidence: 99%
“…A few molecular simulation studies on the simple dipolar liquid‐vapor interface properties exposed to a spatially uniform external field have been carried out recently . It is reasonable to employ uniform electric fields in the studies of the structural and thermodynamic behaviors of bulk water or ices with the periodic boundary conditions applied in the simulation .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Whether this material property can be applied to interfaces of molecular or mesoscopic dimensions has long been a subject of contention. [2][3][4][5][6][7][8] It has long been suggested that an effective dielectric constant of a microscopic interface has to be introduced, and most researchers have agreed that this effective dielectric constant has to be reduced from the bulk value. [9][10][11][12][13][14][15][16][17][18][19] The extent of reduction has mostly remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The DC contribution of the electrical potential difference of each SE before and after (cleaning) the electrochemical cleaning ( Figure 6) showed differences that can be associated with the IP phenomenon. The excitation current produced a progressive reorganization of the electrical charges at the interface until reaching a steady-state potential value in the range of seconds (Shi, et al, 2016). It is worth noting that the potential values closed when they were clean.…”
Section: Electrical Potential Of the Gold Electrode With Respect Tmentioning
confidence: 99%